2015
DOI: 10.3892/ol.2015.3975
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of HER2 and MRP1 are not prognostic factors of long-term survival in 829 patients with esophageal squamous cell carcinoma

Abstract: Abstract. Esophageal squamous cell carcinoma (ESCC)is the eighth most frequent neoplasm in China. However, the expression levels of human epidermal growth factor receptor 2 (HER2) and multidrug resistance protein 1 (MRP1) in patients with ESCC remain to be determined. In the present study, 829 ESCC cases were evaluated using immunohistochemistry. The association between the expression levels of HER2 and MRP1 and the patient's clinicopathological factors was analyzed using Fisher's exact test or χ 2 test. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…High ABCC1 protein expression in pre-treatment tumor biopsies significantly correlated with poor response of EAC patients ( n = 40) to 5-fluorouracil- and cisplatin-based neoadjuvant therapy, while ABCB1 expression had no predictive value in the later study [ 32 ]. However, largest study to date failed to observe any prognostic association for immunohistochemically detected ABCC1 protein expression in tumors from ESCC patients ( n = 829) [ 41 ]. Most recently, correlation of ABCC1 and ABCB1 protein expression with that of Caveolin-1 ( CAV1 , 601047) in tumor tissues from ESCC patients ( n = 84) has been observed and CAV1 expression knockdown also decreased transcript levels of both transporters in ECA-109 cell line in vitro [ 151 ], suggesting a potential interplay between membrane proteins with different functions and their putative use as therapeutic targets.…”
Section: Search Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High ABCC1 protein expression in pre-treatment tumor biopsies significantly correlated with poor response of EAC patients ( n = 40) to 5-fluorouracil- and cisplatin-based neoadjuvant therapy, while ABCB1 expression had no predictive value in the later study [ 32 ]. However, largest study to date failed to observe any prognostic association for immunohistochemically detected ABCC1 protein expression in tumors from ESCC patients ( n = 829) [ 41 ]. Most recently, correlation of ABCC1 and ABCB1 protein expression with that of Caveolin-1 ( CAV1 , 601047) in tumor tissues from ESCC patients ( n = 84) has been observed and CAV1 expression knockdown also decreased transcript levels of both transporters in ECA-109 cell line in vitro [ 151 ], suggesting a potential interplay between membrane proteins with different functions and their putative use as therapeutic targets.…”
Section: Search Results and Discussionmentioning
confidence: 99%
“…Most recently, correlation of ABCC1 and ABCB1 protein expression with that of Caveolin-1 ( CAV1 , 601047) in tumor tissues from ESCC patients ( n = 84) has been observed and CAV1 expression knockdown also decreased transcript levels of both transporters in ECA-109 cell line in vitro [ 151 ], suggesting a potential interplay between membrane proteins with different functions and their putative use as therapeutic targets. In summary, although predictive value of ABCC1 protein expression has been suggested, studies aiming at its prognostic role failed [ 40 , 41 ] and, therefore, other members of the C family and perhaps combinations of more transporters should be followed in the future.…”
Section: Search Results and Discussionmentioning
confidence: 99%
“…However, an increasing number of studies have shown tumor cell resistance to cisplatin, both in vivo and in vitro . This is one of the major factors contributing to treatment failure in ESCC patients . MicroRNAs (miRNAs) are endogenous, small non‐coding RNAs that play an essential role in the regulation of gene expression and tumor progression; in addition, these have been linked to chemotherapy resistance .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 This is one of the major factors contributing to treatment failure in ESCC patients. 19,20 MicroRNAs (miRNAs) are endogenous, small non-coding RNAs that play an essential role in the regulation of gene expression and tumor progression; in addition, these have been linked to chemotherapy resistance. 21 Many studies have suggested that miR-153 is a tumor suppressor miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between HER2 IHC expression and the clinicopathologic characteristics of patients with ESCC is controversial based on data from previous studies. Chen et al reported that HER2 IHC expression levels were associated with gender, tumor size, venous/ lymphatic invasion and HER2 positivity rate was higher in female than in male ESCC patients [19]. In contrast, Gonzaga et al and Sato-Kuwabara et al revealed that there was no correlation between HER2 IHC expression and clinicopathological parameters [2,7].…”
Section: Discussionmentioning
confidence: 98%